Characterization of M4 carbine rifle emissions with three ammunition types. (November 2019) - Aurell, Johanna; Holder, Amara L.; Gullett, Brian K.; McNesby, Kevin; Weinstein, Jason P.
Abstract: Muzzle emissions from firing an M4 carbine rifle in a semi-enclosed chamber were characterized for an array of compounds to provide quantitative data for future studies on potential inhalation exposure and rangeland contamination. Air emissions were characterized for particulate matter (PM) size distribution, composition, and morphology; carbon monoxide (CO); carbon dioxide (CO2 ); energetics; metals; polycyclic aromatic hydrocarbons; and methane. Three types of ammunition were used: a "Legacy" (Vietnam-era) round, the common M855 round (no longer fielded), and its variant, an M855 round with added potassium (K)-based salts to reduce muzzle flash. Average CO concentrations up to 1500 ppm significantly exceeded CO2 concentrations. Emitted particles were in the respirable size range with mass median diameters between 0.33 and 0.58 μm. PM emissions were highest from the M855 salt-added ammunition, likely due to incomplete secondary combustion in the muzzle blast caused by scavenging of combustion radicals by the K salt. Copper (Cu) had the highest emitted metal concentration for all three round formulations, likely originating from the Cu jacket on the bullet. Based on a mass balance analysis of each round's formulation, lead (Pb) was completely emitted for all three round types. This work demonstrated methods for characterizing emissions from gun firing which can distinguish between round-specific effects and can be used to initiate studies of inhalation risk and environmental deposition. Graphical abstract: Image 1 Highlights: Gun firings emit high levels of carbon monoxide and respirable particles. Bullet formulations result in distinctive, measurable emissions. Particle number concentrations were higher than heavy duty diesel trucks. Particles smaller than 1 μm were enriched in lead (Pb). Benzo(a)pyrene is the major contributor to polycyclic aromatic hydrocarbon toxicity. Abstract : Measurement of emissions from an M4 carbine rifle can distinguish between ammunition types for exposure and range contamination studies.